Development of Banyu Lumut Tourism Using Social media - P. Wibowo; R. Febrianti; R. D. Hapsari (Nusantara Science and Technology Proceedings)
The use of social media, especially Instagram, as a media for tourism promotion has been widely applied in various groups in Indonesia, one of them being government institutions. One of our community services is to increase knowledge, awareness, and ability to use social media as a promotion channel for tourist destinations. The problem identified in this paper is the potential of Teagarden embung tourism destinations is not optimal. There is no big concept related to tourism development in Tegaren village and the capacity of human resources that are still not qualified for managing digital media as a means of optimizing tourism promotion. The solution for this problem is categorized into three series, counseling and deepening cooperation, the signing of a Memorandum of Understanding (MoU), and joint development and management. The stages that have been carried out are counseling on the use of social media and assistance in the use of social media as a tourism promotion media for youth organizations and administrators of village-owned enterprises. This is focused on developing tourism promotion for Embung Banyu Lumut located in Tegaren village, Trenggalek district and has resulted in an Instagram account @banyulumut that can be used by the Tegaren village officials to promote embung Banyu Lumut tourism in the future. This program also includes module publications utilizing Instagram as a tourism promotion channel.